A mycoprotein-based high-protein vegan diet supports equivalent daily myofibrillar protein synthesis rates compared with an isonitrogenous omnivorous diet in older adults: a randomised controlled trial. Issue 5 (14th September 2021) - Monteyne, Alistair J.; Dunlop, Mandy V.; Machin, David J.; Coelho, Mariana O. C.; Pavis, George F.; Porter, Craig; Murton, Andrew J.; Abdelrahman, Doaa R.; Dirks, Marlou L.; Stephens, Francis B.; Wall, Benjamin T.
Abstract: Animal-derived dietary protein ingestion and physical activity stimulate myofibrillar protein synthesis rates in older adults. We determined whether a non-animal-derived diet can support daily myofibrillar protein synthesis rates to the same extent as an omnivorous diet. Nineteen healthy older adults (aged 66 (sem 1) years; BMI 24 (sem 1) kg/m 2 ; twelve males, seven females) participated in a randomised, parallel-group, controlled trial during which they consumed a 3-d isoenergetic high-protein (1·8 g/kg body mass per d) diet, where the protein was provided from predominantly (71 %) animal (OMNI; n 9; six males, three females) or exclusively vegan (VEG; n 10; six males, four females; mycoprotein providing 57 % of daily protein intake) sources. During the dietary control period, participants conducted a daily bout of unilateral resistance-type leg extension exercise. Before the dietary control period, participants ingested 400 ml of deuterated water, with 50-ml doses consumed daily thereafter. Saliva samples were collected throughout to determine body water 2 H enrichments, and muscle samples were collected from rested and exercised muscle to determine daily myofibrillar protein synthesis rates. Deuterated water dosing resulted in body water 2 H enrichments of approximately 0·78 (sem 0·03) %. Daily myofibrillar protein synthesis rates were 13 (sem 8) ( P = 0·169) and 12 (sem 4) % ( P = 0·016) greater in the exercised compared with rested leg (1·59 (sem 0·12) v . 1·77 (sem 0·12) and 1·76 (sem 0·14) v . 1·93 (sem 0·12) %/d) in OMNI and VEG groups, respectively. Daily myofibrillar protein synthesis rates did not differ between OMNI and VEG in either rested or exercised muscle ( P > 0·05). Over the course of a 3-d intervention, omnivorous- or vegan-derived dietary protein sources can support equivalent rested and exercised daily myofibrillar protein synthesis rates in healthy older adults consuming a high-protein diet.